The commitment: A determinant basic mental skill in student's performance in Physical Education and Sport - A. Eloirdi; K. Mammad; A. Arfaoui; A. Ahami (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Background and Study Aim: Mental skills and motivation are key factors in learning and performance. This study aims to model their influence on performance in physical education and sport among Moroccan high school students. Material and Methods: A sample of 202 high school students including 100 boys and 102 girls participated in this study. In order to assess mental skills, we used the Ottawa Mental Skills Assessment Tool (OMSAT-3) test and to assess different forms of motivation, we used the Sport Motivation Scale (SMS-28). To evaluate the performance in physical education and sport, we chose an individual sport that is the high jump. Results : The multiple linear regression has as a dependent variable performance in physical education and sport and as explanatory variables mental skills and motivational forms retained only commitment. Conclusion : The commitment, as basic mental skill, is determinant in student's performance in physical education and sport.